Hepatoprotective activity of Parmelia perlata (Huds.) Ach. against CCl4 induced liver toxicity in Albino Wistar rats - Sunita Shailajan, Mayuresh Joshi, Bhavesh Tiwari (Journal of Applied Pharmaceutical Science, 2014)
Many plants have been claimed to possess liver protecting activity. But, due to scarcity of potent modern medicine to treat severe liver diseases, many folk remedies of plant origin have been scientifically evaluated for their potential hepatoprotective activity in experimental animal models. Parmelia perlata (Huds.) Ach. (lichen, Parmeliaceae), commonly known as Dagad phool or stone flower in India, is mentioned in Indian Materia Medica as useful in treating a number of ailments. In the present study, hepatoprotective activity of aqueous slurry of P. perlata was investigated in CCl4 intoxicated Albino Wistar rats and the results were compared with, Silymarin. Intraperitoneal injection of CCl4, produced a marked elevation in the level of biochemical markers such as Serum Glutamate Oxaloacetate Transaminase (SGOT), Serum Glutamate Pyruvate Transaminase (SGPT), bilirubin, cholesterol and triglycerides. Oral administration of P. perlata aqueous slurry at 0.7 g / kg and 1.0 g / kg in CCl4 intoxicated rats showed marked decrease in the level of biochemical markers and results were at par with the effect shown by Silymarin. The results of histopathological analysis were in compliance with the findings of blood biochemical parameter analysis. This study confirms that P. perlata aqueous slurry has phyto-components with hepatoprotective potential.
Keywords: Lichen, Parmelia perlata, Hepatoprotection, Carbon tetrachloride.